Neurological manifestations of organic acid disorders - Hoffmann, Georg F.; Gibson, K. M.; Trefz, Friedrich K.; Nyhan, W. L.; Bremer, Hans J.; Rating, Dietz (European journal of pediatrics, 1994)
Neurological manifestations are very common and can be the leading and/or presenting feature in organic acid disorders, sometimes in the absence of metabolic derangement. Review of the time course and presentation of neurological disease in organic acid disorders reveals characteristic clinical findings of ataxia, myoclonus, extrapyramidal symptoms, metabolic stroke and megalencephaly. A group of organic acid disorders presents exclusively with neurological symptoms. These include glutaryl-CoA dehydrogenase deficiency (glutaric aciduria type I), succinic semialdehyde dehydrogenase deficiency (4-hydroxybutyric aciduria), mevalonic aciduria,n-acetylaspartic aciduria (Canavan disease) andl-2-hydroxyglutaric aciduria. As a group these “cerebral” orgamic acid disorders appear to remain often undiagnosed and their true incidence is much less wellknown than that of the “classical” organic acid disorders. Unfortunately, stringent guidelines for a clinical preselection of neuropaediatric patients to be investigated for organic acid disorders cannot be provided. Today, screening for neurometabolic disorders should be as comprehensive as possible and include determinations of amino acids, purines and pyrimidines and markers of peroxisomal function in addition to organic acid analysis.
Gesehen am 17.06.2024